2020
DOI: 10.31539/bioedusains.v3i2.1849
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Model Pembelajaran Problem Based Learning (PBL) dalam Pembelajaran di Sekolah

Abstract: This study aims to analyze the application of Problem Based Learning (PBL) models in learning in schools. This form of research is literature studies. The method used is descriptive qualitative to analyze the application of Problem Based Learning (PBL) model. Data collection techniques use documentation, by searching journals relevant to Problem Based Learning (PBL) through Sinta and Google Scholar (Google Scholar) with the research journal period of 2015-2020. The keyword used for journal search is the Proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 6 publications
(6 reference statements)
1
8
0
3
Order By: Relevance
“…Interesting Finding Meilasari et al, (2020) The purpose of this study was to analyze the application of the Problem Based Learning (PBL) model in learning in schools.…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…Interesting Finding Meilasari et al, (2020) The purpose of this study was to analyze the application of the Problem Based Learning (PBL) model in learning in schools.…”
Section: Appendixmentioning
confidence: 99%
“…Other researchers concluded that the problem-based learning model focuses students on solving problems independently so that with this activity students will get used to thinking critically and have high-level critical thinking skills. Meilasari et al (2020) in their journal show that there is an effect of using problembased learning models on students' critical thinking skills because learning by applying problem-based learning models can train students to learn independently and think critically. Based on this description, the purpose of this study is to analyze the concept of problem-based learning models, the implementation of problem-based learning models to improve students' critical thinking skills, the effectiveness of problem-based learning models to improve students' critical thinking skills, and the effect of problembased learning models to improve student critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…So there is an influence of the PBL model on students' problem-solving ability. Like his research (Meilasari, 2020), the PBL learning model can increase interest in learning, improve problem-solving abilities, increase learning motivation and critical thinking, and improve learner learning outcomes. (Aidoo et al, 2016) The PBL model greatly develops student process skills, critical thinking, and science process capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of learning in the PBL model lies in the problems that must be solved by students using appropriate material concepts. Students are trained to analyze and solve these problems with their own abilities, while teachers only guide and assist students in the learning process (Meilasari et al, 2020). In PBL activities students are directed to conduct investigations, integrate theory and practice, and be able to use the concepts of knowledge and skills they have to find appropriate problem solving solutions (Savery,2018).…”
Section: ▪ Introductionmentioning
confidence: 99%